Reactivities of Ketone Thiosemicarbazones towards Chloramine-T: A Mechanistic Study - Venkateswaran , V.; Asaithambi, M.; Parimaladevi, P.; Satheeshkum, P. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of thiosemicarbazones by chloramine-T in 30% aqueous acetic acid medium in the presence of perchloric acid has been investigated at 293 K. The rate has first order dependence in [CAT], fractional order in [Substrate] and inverse fractional order in [H3O+]. Addition of the reaction product, p-toluene sulphonamide and variation of ionic strength of the medium have no effect on the rate. An increase in the rate is observed with the decrease in dielectric constant of the medium. Activation parameters have been evaluated from the Eyring plots.The stoichiometric studies reveal that the reactants react in 1 : 5 mole ratio via the formation of a complex.